2019
DOI: 10.1016/j.cell.2019.03.041
|View full text |Cite
|
Sign up to set email alerts
|

An Excitatory Circuit in the Perioculomotor Midbrain for Non-REM Sleep Control

Abstract: Graphical Abstract Highlights d Activity-dependent genetic labeling and gene profiling identify sleep-active neurons d CALCA-expressing glutamatergic neurons in pIII are NREM active and NREM promoting d pIII CCK neurons are NREM promoting and are reciprocally connected to CALCA neurons d Both cell types send long-range excitatory projections to other sleep-promoting areas In BriefIdentification of sleep-active excitatory midbrain neurons that are interconnected and promote sleep via long range projections to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 67 publications
(81 reference statements)
3
32
1
Order By: Relevance
“…On the other hand, one report indicates that under certain pathological conditions Ucn1 and TH can be co-expressed in the human embryonic EWcp [13]. More recently, fluorescent in-situ hybridization (FISH) demonstrated that almost all CCK cells also express the gene Slc17a6 [14], encoding the vesicular glutamate transporter 2 (Vglut2), strongly suggesting that they are also glutamatergic [15,16]. Although almost all CCK-positive cells in the EWcp appear to express Slc17a6, Zhang and colleagues found that there were a number of Slc17a6-positive cells that did not express CCK [14].…”
Section: Neuromodulators Produced In the Ewcpmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, one report indicates that under certain pathological conditions Ucn1 and TH can be co-expressed in the human embryonic EWcp [13]. More recently, fluorescent in-situ hybridization (FISH) demonstrated that almost all CCK cells also express the gene Slc17a6 [14], encoding the vesicular glutamate transporter 2 (Vglut2), strongly suggesting that they are also glutamatergic [15,16]. Although almost all CCK-positive cells in the EWcp appear to express Slc17a6, Zhang and colleagues found that there were a number of Slc17a6-positive cells that did not express CCK [14].…”
Section: Neuromodulators Produced In the Ewcpmentioning
confidence: 99%
“…More recently, fluorescent in-situ hybridization (FISH) demonstrated that almost all CCK cells also express the gene Slc17a6 [14], encoding the vesicular glutamate transporter 2 (Vglut2), strongly suggesting that they are also glutamatergic [15,16]. Although almost all CCK-positive cells in the EWcp appear to express Slc17a6, Zhang and colleagues found that there were a number of Slc17a6-positive cells that did not express CCK [14]. To date it is not known what other neuropeptides these glutamatergic neurons may express, although preliminary data from the Ryabinin lab indicates that adult Vglut2 neurons in the EWcp do not express Ucn1.…”
Section: Neuromodulators Produced In the Ewcpmentioning
confidence: 99%
See 1 more Smart Citation
“…This sleep switch is under the control of arousal that favors wake and inhibits sleep through the suppression of sleep-active neurons by inhibitory wake-active neurons [6,9]. It has been proposed that sleep induction is favored by disinhibition of inhibitory sleep-active neurons [10][11][12]; also, excitatory sleep-active neurons exist that might perhaps present activators of inhibitory sleep-active neurons [13]. However, the forces and mechanisms that flip the sleep switch from wake to sleep when an organism gets sleepy cannot be satisfactorily explained by the present circuit models as it is unclear how sleep-active neurons are turned on when the system is set to sleep.…”
Section: Introductionmentioning
confidence: 99%
“…These neurons reside in the anterior hypothalamus, brain stem, and cortex [6,12]. Excitatory sleep-active neurons were found in the periocular midbrain that project to inhibitory sleep-active neurons in the anterior hypothalamus, the role of which could be to activate inhibitory sleep-active neurons [13]. Studying sleep in less complex brains facilitates sleep circuit analysis.…”
Section: Introductionmentioning
confidence: 99%